Rheumatoid arthritis, multiple sclerosis and lupus: key points from the COVID-19 era - Silva, J. Miguel Vaz D.; Silva, Fatima; Soares, Sandra C. (International Journal of Research in Medical Sciences, 2023)
The purpose of this work was to analyse published data on rheumatoid arthritis (RA), systemic lupus erythematosus (SLE) and multiple sclerosis (MS) and SARS-CoV-2 infection: susceptibility, post-infection autoimmune disease (AD) exacerbation, immunosuppressive therapies and long COVID. Supported by PICO strategy, two independent reviewers conducted the research in the PubMed/Medline database from January 2020 to June 2022 and included 16 articles on RA, 25 on MS and 12 on SLE. The quality assessment of the studies was performed using criteria from the National Institute of Health. Patients with RA or SLE had increased susceptibility to contracting SARS-CoV-2. It was higher in RA and increased with the patients’ comorbidities. For MS, susceptibility to SARS-CoV-2 was similar to the general population. Post-infection AD exacerbation occurred in AR, SLE and MS with an increased number of hospitalisations and deaths. Regarding therapies, in RA the use of glucocorticoids (GC) was associated with a worsening of the infection. A more severe clinical picture was associated with anti-CD20 in SLE and with anti-CD20 and methylprednisolone in MS. Considering long COVID, RA and SLE patients had a higher risk of complications opposite to MS patients. There was a higher susceptibility to SARS-CoV-2 infection in rheumatological diseases AR and SLE, exacerbated by age and comorbidities. For RA and MS, GC aggravated the infection and for SLE and MS anti-CD20 antibodies use. In all AD there was exacerbation and worsening of the clinical picture translated in long COVID, the latter with MS exception.